PENGARUH FAKTOR-FAKTOR KEUANGAN DAN TATA KELOLA PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Jonathan Jonathan; Mungniyati Mungniyati (E-Jurnal Akuntansi TSM, 2023)
This study aims to obtain empirical evidence regarding the variables that affect firm value. The independent variables are the company's size, profitability, leverage, liquidity, capital structure, investment decisions, independent commissioners, institutional ownership, and managerial ownership. This study uses secondary data from financial and annual reports of companies listed on the Indonesia Stock Exchange from 2019 to 2021. It uses a purposive sampling method to select 131 companies that met the criteria. Hypothesis testing uses multiple linear regression analysis through the IBM SPSS Version 2.5. The results of this study indicate that firm size and independent commissioners influence the firm value. On the other hand, profitability, leverage, liquidity, capital structure, investment decisions, institutional ownership, and managerial ownership do not influence firm value.